General and violent recidivism of former forensic psychiatric patients in Finland - Ojansuu, Ilkka; Latvala, Antti; Kautiainen, Hannu; Forsman, Jonas; Tiihonen, Jari; Lähteenvuo, Markku (Frontiers in Psychiatry, 2023)
Background: Forensic psychiatric care in Finland is provided to individuals who have committed a crime due to a serious mental disorder and are in need of psychiatric care. The reconviction (recidivism) rates for this patient group vary in time and between countries, likely due to different treatment practices and requirements for forensic care. Materials and methods: We set out to study criminal recidivism in a national cohort of all patients released from forensic psychiatric care in Finland between 1999-2018. National registries were used to identify the patients and gain information on their criminal sentences. Forensic psychiatric examinations were used to record demographic information for the cohort. The cohort was followed up from hospital discharge to the end of 2019. Results: We identified a total of 501 patients who were released from forensic psychiatric care (mean age: 46.6 years [SD 13.4), 434 (86.6%) were male). The mean and median times spent in treatment for the cohort was 10.0 years [SD 6.5] and 8.7 years respectively. 91% of the patients had schizophrenia spectrum disorder (F2*), and 63.5% had a substance use disorder. A total of 83 patients (16.6%) committed any crime after being released from care, and the mean time to recidivism was 3.8 years. The recidivism rate was 2015 per 100 000 person years. A total of 48 patients (9.6%) committed a violent crime. The mean time to violent recidivism was 4.2 years. The violent recidivism rate was 1083 per 100 000 person years. A longer duration of treatment was associated with a decreased risk of general recidivism (HR 0.95, 95% CI 0.90 to 1.00, p = 0.05). Factors associated with higher recidivism were male sex, having a comorbid substance use disorder and younger age at discharge. Conclusion: The recidivism rate in Finland was markedly lower than has been previously reported for other Western countries, and the mean duration of treatment was also longer. A longer treatment time may reduce risk of criminal recidivism in forensic psychiatric patients. The results suggest, as previous studies have found, that more effort is indicated on the treatment of substance abuse.